Satisfaction with nursing care among past-operative charity patients in surgical words in tertiary hospital in the Philippines - Agravante, Ma. Genia Theresa T.; Aguirre, Ayra Jhoana G.; Banayat, Aprille C.; Buendia, Maria Jill M.; Daya, Mari Francine Krizia B.; Deoso, Regina Gaile G.; Manahan, Jierah R.; Quiat, Joan Leslie A.; Raymundo, Andre P.; Salonga, Raymond D.; San Juan, Ingrid B.; Temporal, Nicolai Ivan M. (Manila College of Nursing University of the Philippines Manila, 2009)
Background. Patient satisfaction, now considered an important patient outcome, a good predictor of patient compliance, and an adequate measure of the quality of health services, is recognized by nurses as a route towards improving nursing care. The researchers also aligned themselves with the goal of the target tertiary hospital towards certification by the International Organization for Standardization, which highlights the desirability of patient satisfaction.

Goal: To determine the components of nursing care and patient characteristics that are associated with the satisfaction of post-operative charity patients in a tertiary hospital in the Philippines.

Methodology
This study followed a descriptive-correlational design, utilizing both qualitative and quantitative data. It took place in the surgical charity wards for males (Ward 2) and females (Ward 4) of a tertiary hospital in the Philippines. Researchers utilized a purposive sampling method to survey a total of 31 participants using interviewer-administered questionnaires. The mean age was 49.1 years old, 61.29% (n=19) were female, 86% (n=26) were married, 39% (n=12) were high school graduates and undergraduates, 35.48% (n=11) were admitted in the ward for 6- 10 days, 22.58% were in their 1% and 2™ post- op day, 58.06% were diagnosed with chronic illnesses, and 35.48% have undergone GS3 type of surgery. Nurses’ performance of nursing care components, (1) the nurse as a provider of caring behaviors, (2) the nurse as an information provider, and (3) the nurse as a technically-skilled provider of physiologic interventions (Sulit, 2007) was measured through the patients’ observation. The. Chi Square Test of independence / Dependence was used to evaluate the association between (1) the dimensions of nursing care and overall evaluation of care and (2) patient characteristics and overall evaluation of care.

Results
Analysis revealed that (1) 26 out of the 31 patients (83.87%) would return to PGH, (2) twenty-seven (87.1%) agreed that nursing care met their expectations, (3) twenty-seven (87.1%) were satisfied overall with nursing care received, and (4) most (90.32%) agreed would recommend PGH to family and friends. Age was associated (a=0.05) with (1) the nurse as an information provider and (2) the nurse as a technically skilled provider of physiologic interventions. Civil status and recommending PGH to family and friends were also associated (a=0.05). The results of the question on additional suggestions to increase satisfaction, classified by dimension were: (1) to increase caring behaviors (n = 14, 45.16%), (2) no other measures were needed (n = 9, 29.03%, and (3) other hospital matters (n = 5, 16.13%). Most (n = 24, 78.42%) responded that they have not encountered incidents that caused dissatisfaction.
Research (In partial fulfillment of the requirements of the course N121.1: Intensive Nursing Experience, Hospital-based) -- University of the Philippines Manila, March 2009.
Keywords: Intensive nursing experience -- Hospital-based.